Moisture damage evaluation using energy based responses - Mehrara, Amir; Khodaii, Ali (Journal of Civil Engineering and Management, 2017)
Monotonic Indirect Tensile tests were performed on asphalt concrete mixtures made of two different types of aggregates. Since the environmental condition is a determining factor in propagation of moisture damage, the effects of temperature and aging were also observed. Three levels of temperature including 4.4 °C, 21.1 °C and 37.8 °C were used in testing. In order to consider the effect of aging, part of the samples were aged according to AASHTO R 30-02 (2010). The parameters of fracture energy, elastic energy and dissipated creep strain energy were obtained for dry and moisture conditioned samples. The sensitivity of the responses to testing parameters was investigated using analysis of variance methods and visual inspections. According to the results, common energy responses cannot be used as realistic criteria to evaluate asphalt mixtures’ moisture damage. To overcome the inadequacy of common energy based responses, modified energy responses were defined using conventional energy based responses normalized by specimens’ failure strain. The analysis of variance showed that the modified energy responses can effectively evaluate the mixtures’ moisture and temperature susceptibility. First published online: 01 Jul 2016